Executive functions of people with drug addiction - Hakeem, Marzia Al; Chowdhury, Kamal Uddin Ahmed (Dhaka University Journal of Biological Sciences, 2020)
This study aimed to see the impairments of executive functions in people with drug dependence. Participants were selected using a purposive sampling method and the sample size was 120, among them 60 were in drug user group and 60 were healthy control. Neuropsychological assessment tools were used – Frontal Assessment Battery (FAB) and Rey-Osterreith Complex Figure Test (RCFT), for assessing the executive functioning of the participants. Data were analyzed using SPSS software, version 20. Independent-Samples t-test was carried out and the result has shown that the control group performed better in all tests. In FAB, significant difference was found in performance between the drug users and control group, t (90.9) = 9.89, p = 0.00, α = 0.01. Both in copy and immediate recall phase of RCFT, there were significant differences of performance between the drug users and control group, t(70.9) = 8.11, p = 0.00, α = 0.01 and t (118) = 11.9, p = 0.00, α = 0.01, respectively. Results indicate that the executive functions of drug dependent people are significantly impaired. Therefore, this issue should be taken in consideration for creating individualized treatment programs and can also assist in taking preventive measures. Dhaka Univ. J. Biol. Sci. 29(1): 27-36, 2020 (January)